2008
DOI: 10.1177/0093854808323678
|View full text |Cite
|
Sign up to set email alerts
|

How “Specific” Are Gender-Specific Rehabilitation Needs? An Empirical Analysis

Abstract: There has been relatively little empirical research on the distinctive characteristics and needs of female offenders that could help guide rehabilitative approaches that are gender specific. This study considered a sample of female offenders ( N = 886) and male offenders ( N = 1,435) who had been released from incarceration and provided with assessment services as part of the community reentry process. Comparisons were conducted using the employment, companions, and financial domains of the Level of Service In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 29 publications
(51 reference statements)
1
68
0
2
Order By: Relevance
“…Female offenders may have trouble keeping full-time employment, which may explain why a high percentage report receiving some sort of public assistance prior to their arrest, report being homeless, or report having lived in shelters at some point during their adulthood . Heilbrun et al (2008) also reported that released female offenders in New Jersey showed higher levels of risk on the financial domain of the Level of Service Inventory than male offenders.…”
Section: Women's Needsmentioning
confidence: 93%
“…Female offenders may have trouble keeping full-time employment, which may explain why a high percentage report receiving some sort of public assistance prior to their arrest, report being homeless, or report having lived in shelters at some point during their adulthood . Heilbrun et al (2008) also reported that released female offenders in New Jersey showed higher levels of risk on the financial domain of the Level of Service Inventory than male offenders.…”
Section: Women's Needsmentioning
confidence: 93%
“…While women still represent a minority of the forensic psychiatric and prison population, the number of women committing violent crimes has increased steadily over the past two decades (Heilbrun et al, 2008;Odgers, Moretti, & Reppucci, 2005). Moreover, some types of violence, such as domestic and inpatient violence seem to be as common in women as in men (Nicholls, Brink, Greaves, ABSTRACT To gain insight into the relatively small, but increasing group of women in forensic psychiatry, a retrospective multicentre study was started gathering information from the files of 275 female patients of four Dutch forensic psychiatric hospitals on characteristics and violence risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Bartlett, Jhanjib, Whitec, & Harty, 2014;Blanchette & Brown, 2006;Covington & Bloom, 2006;Heilbrun et al, 2008;Long, Fulton, & Hollin, 2008). In general, these treatment models stress the importance of using gender-sensitive risk assessment and addressing issues such as trauma, (sexual) abuse, and the role of social relations and disruptions in these relations Downloaded by [Orta Dogu Teknik Universitesi] at 09:54 30 December 2015 during treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Although women represent a smaller proportion of the penitentiary population compared to men, in the past two decades violence by girls and women has increased internationally (Heilbrun et al, 2008;Odgers, Moretti, & Reppucci, 2005). In the Netherlands, women are a minority within the penitentiary system and the forensic psychiatric care system, but recent surveys showed an increase over the last 30 years from about 4% in forensic residential care in the 1980s to 7% in 2011, and 9% inflow in 2011 (DJI, 2012a;Lammers & de Vogel, 2012).…”
Section: Female Offendersmentioning
confidence: 99%